2010
DOI: 10.1007/s10549-010-1316-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different approaches for assessment of HER2 expression on protein and mRNA level: prediction of chemotherapy response in the neoadjuvant GeparTrio trial (NCT00544765)

Abstract: Introduction: Human epidermal growth factor receptor 2 (HER2) testing is an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 35 publications
2
32
0
5
Order By: Relevance
“…To the best of our knowledge with more than 1,000 ILCs, this is the largest cohort of neoadjuvant treated lobular carcinomas to date. The number of pCRs in the ILC group [31,32]. The rate of HER2-positive ILC is higher compared to data from the HERA trial [33].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…To the best of our knowledge with more than 1,000 ILCs, this is the largest cohort of neoadjuvant treated lobular carcinomas to date. The number of pCRs in the ILC group [31,32]. The rate of HER2-positive ILC is higher compared to data from the HERA trial [33].…”
Section: Discussionmentioning
confidence: 82%
“…In the older neoadjuvant trialsHER2-testing was not established as a routine method. This might explain the higher rate of HER2-positive cases compared to HERA [31]. In addition, we have performed central histology assessment in a subset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,8,11,19,20 Despite 410 years of routine HER2 testing, studies have demonstrated variability in HER2 positivity assessments between local pathology laboratories and central testing centers, posing a challenge for clinicians. 15,[21][22][23][24][25] In some of these studies it was assumed that variations in HER2 positivity at individual centers equated to problems with testing quality. 15,22,26,27 To overcome this issue, monitoring of HER2 positivity rates has been suggested as a means for HER2 testing quality control in international guidelines.…”
mentioning
confidence: 99%
“…Moreover, switching to four NX courses had a better toxicity profile than continuing TAC. The rates of pCR in both groups were low (5.3% in the TAC arm vs 6% in the NX arm) [28][29][30]. Other studies have tested the approach of response-adjusted sequential therapy, however, this remains to be investigated [31].…”
Section: Therapeutic Optionsmentioning
confidence: 99%